The relationship between intellectual ability and auditory multitalker speech perception in neurodivergent individuals - Bonnie K. Lau; Katherine Emmons; Ross K. Maddox; Annette Estes; Stephen R. Dager; Susan J. (Astley) Hemingway; Adrian K. C. Lee (PLoS ONE, 2025)
The ability to selectively attend to one talker in the presence of competing talkers is crucial to communication in noisy, real-world environments. In this study, we investigated the relationship between intellectual ability and speech perception under multitalker conditions. Since neurodivergent individuals show a wide range of intellectual ability, from above average IQ to intellectual disability, intellectual ability may be an important individual characteristic that impacts multitalker speech perception, but this is not currently well understood. We tested individuals with autism, fetal alcohol spectrum disorder, and an age- and sex-matched comparison group, all with typical hearing. We found a strong positive correlation between IQ and multitalker speech perception thresholds. This demonstrates that deficits in intellectual ability, despite intact peripheral encoding of sound, are associated with difficulty listening under complex conditions for individuals with autism and fetal alcohol spectrum disorder. Future research is needed to investigate specific cognitive control mechanisms that contribute to difficulty listening under complex conditions. These findings suggest that audiological services to improve communication in real-world environments for neurodivergent individuals should be considered during clinical evaluations.